A framework for heart-lung interaction and its application to prone position in the acute respiratory distress syndrome - Kenny, Jon-Emile S. (Frontiers in Physiology, 2023)
While both cardiac output (Qcirculatory) and right atrial pressure (PRA) are important measures in the intensive care unit (ICU), they are outputs of the system and not determinants. That is to say, in a model of the circulation wherein venous return and cardiac function find equilibrium at an ‘operating point’ (OP, defined by the PRA on the x-axis and Qcirculatory on the y-axis) both the PRA and Qcirculatory are, necessarily, dependent variables. A simplified geometrical approximation of Guyton’s model is put forth to illustrate that the independent variables of the system are: 1) the mean systemic filling pressure (PMSF), 2) the pressure within the pericardium (PPC), 3) cardiac function and 4) the resistance to venous return. Classifying independent and dependent variables is clinically-important for therapeutic control of the circulation. Recent investigations in patients with acute respiratory distress syndrome (ARDS) have illuminated how PMSF, cardiac function and the resistance to venous return change when placing a patient in prone. Moreover, the location of the OP at baseline and the intimate physiological link between the heart and the lungs also mediate how the PRA and Qcirculatory respond to prone position. Whereas turning a patient from supine to prone is the focus of this discussion, the principles described within the framework apply equally-well to other more common ICU interventions including, but not limited to, ventilator management, initiating vasoactive medications and providing intravenous fluids.